Sosialisasi dan Inovasi Mesin Pengurai Sabut Kelapa Guna Meningkatkan Kualitas dan Produktifitas Industri Sabut Kelapa di Desa Lamnga Kecamatan Mesjid Raya Aceh Besar - Bahri, Idal; Pangastuti, Yunida; Husaini; Putra, T. Edisah (Yayasan Kawanad, 2022)
The management of the industrial partner practically runs naturally without a touch of technology & good business management. The existence of this coir industry/entrepreneur on the environment is very important. This means that this industry is very helpful to the people in the village, because it absorbs workers. Based on the results of the situation analysis from partner industries, the problem that needs to be solved is that there is no working tool in the form of a reliable coconut coir combing machine, which has a low failure rate for mass decomposed coir. The method offered in this program is the applicative method, meaning that it is approached by scientific methods that apply in the process of designing and manufacturing products or tools. This fiber combing machine has a capacity of 10,000 coconuts per day, or 1250 pieces per hour. This machine will later be donated/given to entrepreneurs/coconut craft industry. The purpose of this activity is to assist partner industries in increasing the production capacity of coconut coir woven between 20-25 times compared to conventional systems. There are still many human resources in the